Prioritisation approach to score and rank synthetic musk compounds for environmental risk assessment. Issue 9 (29th January 2015) - Homem, Vera; Silva, José Avelino; Ratola, Nuno; Santos, Lúcia; Alves, Arminda
Abstract BACKGROUND Synthetic musks are massively used in personal care and cosmetic products and they reach the environment mainly because they are not completely removed in wastewater treatment plants (WWTPs). In this work, an innovative and simple chemical scoring and ranking approach was developed as a screening tool to evaluate the overall impact of musks on the environment, identifying priority compounds. This system is idealised as an important tool for a subsequently feasible environmental risk assessment of musks that may represent the overall contamination on a regional scale. RESULTS Physicochemical and toxicological properties of 18 synthetic musks estimated by (Q)SAR were successfully used for the chemical scoring and combined with observed data to estimate the environmental impact posed by these compounds on four environmental compartments. CONCLUSION The prioritisation approach for musks shows that the risk of a compound can vary depending on the compartments, although HHCB posed a high to very high risk to all of them. For instance, AHMI has a relevant risk to soil and air, but very low to low in water and sediments, while AHTN was considered to be of medium risk for water and soil, but of a very high risk to sediments and air. © 2015 Society of Chemical Industry